Rethinking social reproduction in the time of COVID-19 - Dattani, Kavita (The Journal of Australian Political Economy, 2020)
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; care; covid-19; discipline; genre; géographie; périodes historiques; ressource en ligne; sciences humaines; thématiques; travail; travail domestique; violences

The Routledge handbook of gender and violence - Lombard, Nancy (Routledge handbooks, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

La ville, faite par et pour les hommes : dans l'espace urbain, une mixité en trompe-l'œil - Raibaud, Yves (Égale à égal, 2015)
Des noms d'hommes sur les plaques à tous les coins de rues. Des loisirs qui profitent en priorité aux garçons. Des offres de transport insensibles aux spécificités de genre. Sans oublier la culture du harcèlement.La ville se décline surtout au masculin. Plusieurs études récentes le confirment. L'auteur décrit comment la cité renforce les inégalités entre les femmes et les hommes et en crée de nouvelles, et montre qu'il est possible de la rendre plus égalitaire.
Keywords: discipline; domination masculine; environnement; europe; france; géographie; géographie du genre; organisation des villes; projet charge mentale; régions géographiques; sciences humaines; thématiques; violences; violences envers les femmes*